The Berenstain bears and the drug free zone - Berenstain, Stan, 1923-; Berenstain, Jan, 1923- (New York : Random House, 1993)
Brother and Sister Bear try to solve the mystery of how illegal drugs are getting into their school.
Keywords: Drug abuse -- Fiction; Bears -- Fiction; Mystery and detective stories